Positional synchronization affects physical and physiological responses to preseason in professional football (soccer) - Folgado, H.; Goncalves, B.; Sampaio, J. (Research in Sports Medicine, 2018)
This study aimed to identify changes in tactical, physical and physiological performances in large-sided games during the preseason of elite footballers. Thirty professional football players participated in several GK+8vs.8+GK large-sided games across the first four weeks of the season. Players were monitored by GPS units and heart rate monitors to quantify physical, physiological and tactical performances. The variables were compared according to the preseason period, players` positioning and professional experience. The training situation promoted similar physiological responses during the first and the last training period. However, players were revealed to have higher levels of positional synchronization during the last preseason period, indicating an improved tactical performance. Tactical variables seem to reflect the improvement of players` performance during the preseason, measured in large-sided games situation, while affecting both physical and physiological demands. These results highlight the potential of positioning derived variables, concurrently to physical and physiological variables, for football training optimization.